2018
DOI: 10.1039/c8dt03768j
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the development of luminescent lanthanide-based supramolecular polymers and soft materials

Abstract: Here we discuss the emerging field of luminescent lanthanide-based soft materials with our focus on the different approaches used for their design and synthesis as well as manipulations of their functional properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…[2][3][4][5][6][7] These characteristics have led to these compounds being used as sensors, 7 imaging agents, 7 lasers, 8 optical displays, 8 and multi-emissive materials. 4,6,9 Multi-emissive materials (in this context materials either made up of multiple Ln 3+ containing molecular species or molecular species containing two or more Ln 3+ ions) [10][11][12][13][14][15][16][17] in particular are high value targets owing to their propensity towards more advanced and complex applications including molecular barcodes, 12 ratiometric sensors, 13 molecular logic gates 18 and white emissive solids. 14,16,19 To translate into functional materials, it is desirable to immobilise Ln 3+ multiemissive species onto surfaces, however only limited examples exist of surface immobilised multi-emissive species.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7] These characteristics have led to these compounds being used as sensors, 7 imaging agents, 7 lasers, 8 optical displays, 8 and multi-emissive materials. 4,6,9 Multi-emissive materials (in this context materials either made up of multiple Ln 3+ containing molecular species or molecular species containing two or more Ln 3+ ions) [10][11][12][13][14][15][16][17] in particular are high value targets owing to their propensity towards more advanced and complex applications including molecular barcodes, 12 ratiometric sensors, 13 molecular logic gates 18 and white emissive solids. 14,16,19 To translate into functional materials, it is desirable to immobilise Ln 3+ multiemissive species onto surfaces, however only limited examples exist of surface immobilised multi-emissive species.…”
mentioning
confidence: 99%
“…They can be extensively used in various applications, such as optoelectronics devices, eld-effect transistors, detectors, medical diagnosis, bio-imaging, etc. [112][113][114]. Hence, luminescent gels have been paid much attention due to their outstanding biocompatibility and viscoelastic properties [115].…”
Section: Anti-counterfeiting Applicationsmentioning
confidence: 99%
“…Lanthanides, or rare earths, compose the 5d block of the periodic table. Most Ln(III) ions are luminescent and play a vital role in lighting and light conversion (Ozawa and Itoh, 2003 ; Kotova et al, 2018 ), and tpy and tpy-like ligands showed several interesting luminescent properties when combined with lanthanide ions (Beck and Rowan, 2003 ). Ghosh et al ( 2015 ) reported the multicolor luminescent properties of elastin-like polymers (ELPs) with tpy derivatives incorporated into their side chains.…”
Section: Light-emitting Materialsmentioning
confidence: 99%